Internship Factors and Career Path Clarity: The Role of Organizational Context and Career Decidedness - John Kirby Z. Añonuevo Añonuevo; Shaira Shayne L. Ybañez; Jariene Fibelle Mae T. Alonzo; Kylens D. Bajade; Noriella P. Gereña; Jannah Carmelle B. Cabal; Lalaine O. Narsico; Peter G. Narsico (Future Science / FSH-PH Publications, 2026)
This study was conducted to examine the relationship between variables related to internship and clarity of career path among university students who completed On-the-Job Training (OJT). Data were collected using a quantitative descriptive-correlational design for 149 participants in six constructs: internship experience, work environment, personal impact, company size and structure, career decidedness, and career clarity. We used descriptive statistics, Spearman’s correlation and multiple regression analyses. The findings revealed that internship experience, work environment and personal impact were all significantly associated with career clarity, with personal impact having the strongest association. However, only company size and structure and career decidedness were significant predictors in the regression model. The results underscore the importance of organizational context and the clarity of prior career in affecting students’ career development. The findings indicate that well-structured internship opportunities, positive work environments and effective matching between students and host organizations can lead to better career clarity and employability outcomes. Future research may address limitations by employing longitudinal designs and broader institutional contexts.